A házépítések (anti)szociális támogatásának krónikája - Lengyel, Imre (Tér és Társadalom, 1991)
In my study, I analyze the most important characteristics of housing construction in Hungary between 1970 and 1989 by regional and seftlement types. In my investigations, I put special emphasis on two fields of housing policy: the changes of the amount of social subsidies given to private housing construction, and the conditions of getting construction loans under favourable terms. During the period examined, housing constructions can be grouped into three types by their financial resources: 1. Construction of state-owned flats. Their construction costs were fully covered from the state (council) budget. The rents of these flats were low, and did not even cover the maintenance costs (in the capital city, these flats could be re-rented to sub-tenants for ten-times more than the offlcial rent). 2. Construction of private flats which were sold to individuals. In this case, the council had the right to select the purchaser on the basis of „socio-political" principles. (This is a kind of quasi-market type housing.) Their construction costs were covered up to 40% from the state budget. The buyer had to pay 10% of the purchase price in cash, and could get state loans under favourable terms to cover the rest of price. 3. Construction of owner-occupied private flats/houses. When buying or constructing these flats/houses, the buyer had to pay 30-50 % of the construction costs in cash. For the remaining amount, either state loan under favourable terms could be drawn, or – depending on the number of children – non-repayable social subsidy could be received. State housing and private flats sold to the individuals by the local councils were primarily built with the purpose of solving the housing problems of socially needy people (we have to note, that until the end of the 1980s, one family could only buy or rent from the state one flat/house only, so there could not be more than one flat/house in the property of one family). The investigations have, however, proved, that the first two types of flats were almost exclusively built in Budapest and the bigger towns, while their construction was very rare in smaller towns and villages, where close to 50 % of Hungary’s population lives. At the end of 1989, state housing in Budapest gave 58 % of all flats, while this proportion was 25 % in other towns and only 1.2 % in the villages. These data, as opposed to the findings of another investigation proving that 19 % of the population in the villages, 7 % in the towns and only 3 % in Budapest was deprivated, prove that housing policy did not meet socio-political requirements. Until the end of the 1970s, private housing construction was only tolerated by the official housing policy, because it supported state housing construction – in harmony with the prevailing ideology and in favour of state ownership. At around 1980 it became clear, that the state budget could not cover the costs of housing construction projects. As a result, the government started to promote and financially support private housing construction as well. By 1989, state housing construction practically ceased to exist, while in the 1970s this type gave one-third or even half of all flats constructed. In the cases of owner-occupied, or private flats, two different categories can be differentiated by the amount/type of state subsidies. One of them is the group of privately-owned flats in multistory blocks of flats and the other is family houses. They could either be given state subsidy on the basis of the number of children, or long-term loans under favourable conditions. Official housing policy judged the above two categories differently. Until 1983, non-repayable state subsidy drawable according to the number of children was only due to those who purchased privately-owned flats in blocks of flats (having two children, the amount of this subsidy gave about 8-10% of the flat’s purchase price), and it was not granted for the construction of family houses. Until 1988, the amount of long-term loans that could be received for the construction of family houses was also lower than for the private flats. In addition to that, the repayment period was shorter, and the rate of interest higher, though it was still lower than the real interest rate. Another type of strong negative preferencies was cused by the fact, that the amount of loans that could be drawn was bigger in the town than in the villages. When investigating the construction of private flats we find, that in Budapest, the number of private flats in multi-story blocks of flats was three-times higher than that of the family houses, while it was 1.5-times higher in other towns, and only one-tenth in villages. State budget, and state housing policy subsidized the capital city and the large towns both in the construction of state housing and private housing, and the village-dwellers were left alone with their housing problems. In the development of infrastructure, similar aspects and proportions prevailed as in housing construction. All the above were, naturally, supported by ideological arguments, stating the superiority of the working class to peasantry, and the bigger importance of towns to villages. These, however, did not decrease the expectations of people to housing, and the lack of proper housing was reproduced by those who moved into the towns due to these problems. Besides the attitude resulting from the ideology, we are faced with the successful lobbying of the construction industry and the factories manufacturing pre-fabricated elements. Multi-story blocks of privatee flats could only be constructed by state companies, and this way these companies could build concentrated urban housing estates favourable for them so that their extremely high costs and poor-quality performance was always covered by the state budget Finally, state subsidy of private housing ended its way at the state construction industry and the background industries. Regional characteristics of housing construction show, that this is the population of the basically agricultural Great Hungarian Plain, where there are very few towns, which used their own resources at the housing constructions to the highest extent to the disadvantage of their consumption and savings. The debts of people living in this region are the biggest, while their incomes lag far behind the average of other regions. In addition to this, family houses, as a form of real-estate savings, are highly devaluated by the housing market these days, because the vast majority of necessary infrastructure is missing. State housing constructed earlier will sell the majority of them to their actual inhabitants. However, as a consequence of disproportional housing constructions, there is hardly any state housing in the smaller towns and villages: there is not enough state housing to satisfy the socially needy people, how could there be enough for sale, thus increasing the incomes of the local governments. As a conclusion we can draw, that the changes in the political system preserved the previous privileges in the ownership of flats/houses and increased further the differences between the towns and villages. The lack of social housing in the villages forces the poor, deprivated people to the towns, who increase urban problems and thus create another „catch 22".